Preoperative Low Prealbumin Is Associated With Recurrence in Patients With Stage II/III Gastric Cancer After Laparoscopic D2 Gastrectomy - Gao, Chun; Dan Zeng, Ci Dian; Tong, Yi Xin; Zhu, Li; Zhang, Sheng (Frontiers in Surgery, 2022)
Background Postoperative recurrence is associated with poor prognosis in patients with gastric cancer. This study aimed to explore predictive factors contributing to recurrence in patients with stage II/III gastric cancer after laparoscopic D2 gastrectomy. Methods This retrospective study was conducted at a single tertiary referral hospital. Patients diagnosed with gastric cancer who met the inclusion criteria were included in the study. The clinicopathological characteristics of the patients were collected. The patients were divided into recurrence and non-recurrence groups. The predictive factors were investigated using univariate and multivariate analyses. Results In total, 462 patients were included. The incidence of recurrence was 26.4% (122/462) in all patients. The most common recurrence pattern was haematogenous recurrence. In the multivariate analysis, the independent predictive factors for recurrence were serum prealbumin level (p < 0.001), prognostic nutritional index (p = 0.001), carbohydrate antigen 19-9 (CA19-9) (p < 0.001), number of lymph node metastases (p < 0.001), signet-ring cell carcinoma (p = 0.001), tumor deposit (p = 0.001), and no/incomplete adjuvant chemotherapy (p < 0.001). Conclusions Our findings revealed that nutritional status was an independent predictive factor for recurrence in patients with gastric cancer after D2 gastrectomy. We suggest that patients with risk factors for recurrence receive both nutritional support and intense surveillance.